Unveiling and verification of mitochondria-related genes as potential diagnostic biomarkers in ulcerative colitis based on bioinformatics analysis and experimental validation - Hongliang Chen; Ning Li; Xuerong Liu; Mingyu Ran; Xinyu Geng; Jihan Qi; Jiawei Qiu; Xueyu Cang; Shiling Huang; Yingying Tian; Ram Prasad Chaulagain; Shizhu Jin (PLoS ONE, 2025)
Immune dysregulation is a pathogenic factor in ulcerative colitis (UC), in which mitochondrial involvement is increasingly recognized. This study aimed to construct a diagnostic model using mitochondria-related genes, identify new target genes, and illuminate the roles of mitochondria-related genes in energy metabolism, immune infiltration and the pathogenesis of UC. RNA expression data from 465 patients with UC and 154 healthy controls (HCs) were obtained from the GEO database. A total of 128 mitochondria-related differentially expressed genes (Mito-DEGs) were identified between patients with UC and HCs. A diagnostic model constructed from 20 genes showed satisfactory discrimination, calibration functions, clinical benefits and clinical impacts. Enrichment and immune infiltration analyses revealed significant differences in mitochondrial structure and function, immune cell disorders, and signaling pathway activation between the high- and low-mitochondrial gene expression UC groups. Correlations between mitochondrial structure and function and immune cells were evaluated. Single-cell RNA sequencing data were used to analyze the hub gene distribution, cell‒cell communication, and enrichment. Cell‒cell communication analysis revealed that immune response and pathogenesis pathways are activated in UC. Experiments revealed that the expression of the ACADM and ACADSB genes was decreased in UC patients. Mitochondrial dysfunction contributes to the pathogenesis of UC by altering energy metabolism, promoting immune disorders and activating pathogenic signaling pathways. The mitochondria-related genes are valuable for the diagnosis of UC. ACADM and ACADSB may play important roles in UC pathogenesis.